2023
DOI: 10.3389/fimmu.2023.1213246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-reactive protein with distinct hyperinflammatory biomarkers in association with COVID-19 severity, mortality and SARS-CoV-2 variants

Abstract: C-reactive protein (CRP) has been one of the most investigated inflammatory-biomarkers during the ongoing COVID-19 pandemics caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The severe outcome among patients with SARS-CoV-2 infection is closely related to the cytokine storm and the hyperinflammation responsible for the acute respiratory distress syndrome and multiple organ failure. It still remains a challenge to determine which of the hyperinflammatory biomarkers and cytokines are the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The elevated levels of IL-1β, MCP-1, and IL-6 in the spinal dorsal horn of the SCN-CCI group are consistent with the involvement of neuroinflammation in NP. These cytokines have been implicated in mediating glial activation, neuroinflammatory responses, and the sensitization of pain pathways ( Hester et al, 2022 ; Damiati et al, 2023 ; Paranga et al, 2023 ), and the increased activation of microglial cells observed in the SCN-CCI group further supports the role of neuroinflammation in NP pathophysiology. Microglial activation has been associated with releasing pro-inflammatory mediators and amplifying pain signaling ( Dheen et al, 2007 ; Smith et al, 2012 ).…”
Section: Discussionmentioning
confidence: 73%
“…The elevated levels of IL-1β, MCP-1, and IL-6 in the spinal dorsal horn of the SCN-CCI group are consistent with the involvement of neuroinflammation in NP. These cytokines have been implicated in mediating glial activation, neuroinflammatory responses, and the sensitization of pain pathways ( Hester et al, 2022 ; Damiati et al, 2023 ; Paranga et al, 2023 ), and the increased activation of microglial cells observed in the SCN-CCI group further supports the role of neuroinflammation in NP pathophysiology. Microglial activation has been associated with releasing pro-inflammatory mediators and amplifying pain signaling ( Dheen et al, 2007 ; Smith et al, 2012 ).…”
Section: Discussionmentioning
confidence: 73%
“…The CRP levels were also found to be highly associated to immunological alterations as a marked rise in pro-inflammatory biomarkers 46 . Although CRP is mostly produced in the liver, its mRNA has been found in respiratory tract epithelial cells and T-lymphocytes 47 .…”
Section: Discussionmentioning
confidence: 98%
“…The major laboratory markers that were studied by Romanian authors are displayed in Table 1. Yes, even more so in Roma [53,54,[58][59][60][61][62]70] Diabetes [48,94] Antiphospholipid syndrome [47] Hypertension [27] Cardiac dysfunction [46,73,93] Overweight/metabolic syndrome [27,54,93] Lung involvement [50,57] PIMS [83] Chronic Spontaneous Urticaria Exacerbation [42] Pneumothorax/ pneumomediastinum [31,72] Liver failure [44] Multiple organ dysfunction [ [57,58,102,103] No [55] More comorbidities [29,101] Lung involvement [57] In addition, this article aimed to identify gaps in this research and provide encouragement for Romanian research to focus on novel and detailed aspects of the pandemic. For instance, as Romania grapples with the aftermath of the COVID-19 pandemic, understanding the long-term effects of the disease is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%